Nanoplasmonics - Klimov, Vasily ( Vasiliĭ Vasilʹevich) (Pan Stanford Pub, 2014)
The nanoplasmonics is part of nano-optics and nanotechnology and deals with oscillation of conduction electrons in nanoparticles and nanostructures. This book comprises theoretical and experimental analysis of plasmonic properties of nanoparticles of different shape and made of different materials